Quality of Distance Education in Turkey: Preschool Teacher Training Case - Gültekin, Mehmet (International Review of Research in Open and Distributed Learning, 2009)
Distance education is used for teacher training at different levels and fields in Turkey. Launched in the 2000-2001 academic year and still applied by Anadolu University, the Pre-School Teacher Training Program is one of those programs offered by distance education. This study aims to evaluate Anadolu University’s Preschool Teacher Training Program in Turkey by obtaining student opinions. A total of 1,026 senior students enrolled in the Preschool Education major at the Open Education Faculty of Anadolu University participated in the survey. A questionnaire to determine the opinions of students on the program was used as a means of data collection. Means (X) and standard deviations (SD) were employed to analyze the survey data. The results showed that although the teacher candidates study at a good level, they do not have a good record of watching the television programs. The results also revealed that the opinions of teacher candidates about the textbooks, television programs, teaching practices, and academic assistance services are positive.